Eksistensi Gerakan Boikot Produk Perancis sebagai Respon Terhadap Majalah Carlie Hebdo dan Islamophobia di Prancis - Aulia Ayu Fernanda; Hermini Susiatiningsih; Muhammad Faizal Alfian (Journal of International Relations Diponegoro, 2022)
Islamophobia has been rife in Europe, including in France, the emergence of Islamophobia has caused a lot of concern for Islamic communities in the world. The development of Islamophobic acts in France has resulted in a lot of chaos and negative sentiments by the world community, especially globally, towards French society. Until the emergence of Charlie Hebdo magazine which publishes a controversial article which is considered to be ridiculing the Prophet Muhammad, it has finally caused criticism for Muslims, especially in the Middle East. Muslims argue that what has been written in Charlie Hebdo magazine is blasphemy. Prophet Muhammad SAW is considered a role model for the Muslim community so no one should be able to give unfounded criticism. The people of the Middle East as a region with a Muslim majority finally responded to this phenomenon. In this paper, we will examine how the Middle East responds to the phenomenon carried out by Charlie Hebdo. This study uses the concept of a new social movement to see the movements carried out by the Middle East and the impact on the response of Muslim communities around the world.